Scholarship Overview on Gnosticism and Early Jewish-Christian Writings: (re)mantling Categories about Ancient Religious Phenomena (Revista Archai, 2018)
Gnosticism as an organized social movement with a coherent and uniform message is an ambiguous terminology. However, the existence of distinct elements that are simultaneously present in texts established as gnostic and New Testament writings is unquestionable. There is a primeval milieu shared among particular communities based on several literary receptions in which diverse ancient religious phenomena, gradually, became consolidated. Critical studies reveal a mandatory revaluation of modern scholarship categories, including essential terms such as Gnosticism and Gnosis; terminological references and religious expressions in the first century do not exclude the presence of shared ideas within the Christian Testament and other Jewish mythic configurations. There are multiple understandings and applications of the term Gnosticism in contemporary scholarship, including those which deliberate evident issues of definition. As a result, a brief scholarship review regarding selected dimensions of Gnostic ideas in the ancient Mediterranean context provides historical and literary grounds for textual analysis in the Jewish-Christian mythmaking and the reception processes of biblical writings in the ancient world. Consequently, by dis-mantling and re-mantling these ancient religious horizons, scholars consider a comprehensive approach of the ancient Hellenistic religious phenomena in which elements from Gnosticism, Apocalypticism, Ancient Magic and Mystery Religions share historical contexts and furnish complex symbolic communications in their specific textual expressions.